Konflik Moro Sebagai Ancaman Identitas Nasional Filipina Selatan dan Dampaknya pada Kohesi Politik ASEAN - Dewi Erlina; Elly Nurlia (Department of International Relations, Brawijaya University, 2025)
The Moro conflict in the Southern Philippines is rooted in postcolonial structural marginalization and failed integration, posing a serious threat to Philippine national identity. The purpose of this study is to analyze the Moro conflict as a threat to national identity and its impact on ASEAN political cohesion, using Benedict Anderson's Imagined Communities Theory framework. The method used is a qualitative literature study approach, as data collection utilized secondary data analysis from credible journals and academic documents. The results show that the failure of the Philippine national narrative to create bonds of equal solidarity, as envisioned by Anderson, has triggered the emergence of a separate